Fasilitasi Senam Zumba Pada Komunitas Desa Gumpang Jaya Kabupaten Aceh Tenggara - Melfa Br Nababan; Fakhrur Rizal; Karmila Sari; Adelia Putri Pane (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Recreational sports are basically carried out to fill free time, with the main aim to relax (relaxation) and enable social interaction. Recreational sports also teach a person to fill his free time with positive activities, that is, not to harm himself, others or the environment. In addition, recreational sports also help prevent negative activities such as drug use, van use, and so on. To help the people of Gumpang Jaya Village, Southeast Aceh District develop a healthy lifestyle and social interaction, the community will hold a socialization of Zumba exercises. With this event, people can spend their spare time in a useful way while adopting a healthy, fit and active lifestyle.